2016
DOI: 10.1021/acs.molpharmaceut.5b00861
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Modeling of Gastrointestinal Drug Absorption: Predictive Performance of Three Physiologically Based Absorption Models

Abstract: Gastrointestinal (GI) drug absorption is a complex process determined by formulation, physicochemical and biopharmaceutical factors, and GI physiology. Physiologically based in silico absorption models have emerged as a widely used and promising supplement to traditional in vitro assays and preclinical in vivo studies. However, there remains a lack of comparative studies between different models. The aim of this study was to explore the strengths and limitations of the in silico absorption models Simcyp 13.1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 49 publications
(109 reference statements)
1
98
1
Order By: Relevance
“…After confirming that mixing of the organic layer with Level II FaSSIF components has minimal effect, if any, this study showed that biphasic experiments are useful for estimating PRC values of dipyridamole and ketoconazole. Based on the comparison of the resulted simulated plasma profiles with the actual plasma profiles in adults, estimations were better than those from the D-P data or the default values of the Simcyp software, which have previously been employed to model drug precipitation [47]. Biphasic experiments were also useful for estimating PRC values of itraconazole; for Sporanox ® OS, subsequent plasma simulations were better than using default PRC values in the Simcyp software.…”
Section: Resultsmentioning
confidence: 99%
“…After confirming that mixing of the organic layer with Level II FaSSIF components has minimal effect, if any, this study showed that biphasic experiments are useful for estimating PRC values of dipyridamole and ketoconazole. Based on the comparison of the resulted simulated plasma profiles with the actual plasma profiles in adults, estimations were better than those from the D-P data or the default values of the Simcyp software, which have previously been employed to model drug precipitation [47]. Biphasic experiments were also useful for estimating PRC values of itraconazole; for Sporanox ® OS, subsequent plasma simulations were better than using default PRC values in the Simcyp software.…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, the pharmacokinetic parameters AUC, Tmax and Cmax were assessed in terms of the fold error between the observed and the predicted values, according to equation (1). As it is widely applied within pharmaceutical industries, a two-fold error was considered to be an acceptable prediction [46][47][48][49][50][51][52]…”
Section: Resultsmentioning
confidence: 99%
“…3), traditionally used in clinical trial design, are now being developed and used in earlier stages of discovery and development across industries. PBPK models require in vitro ADME data in addition to information about the physical and chemical properties of a compound reconstructed in vitro models (Muoth et al, 2016) to chip-based technologies (Picollet-D'hahan et al, 2016), new generation of parallel artificial membrane permeability assays (PAMPA) (Chen et al, 2008) and in silico modeling of gastrointestinal absorption approaches with validated commercial models (Gozalbes et al, 2011;Sjögren et al, 2016). An international group of experts in the field of epithelial barriers was convened from academia, industry, and regulatory bodies to present both the state-of-the-art of non-animal models of the skin, intestinal, and pulmonary barriers and to discuss research-based, industry-driven, and regulatory-relevant directions for both the development of new models and the refinement of existing test methods.…”
Section: Pharmacokinetic Modeling Of the In Vivo Situationmentioning
confidence: 99%